KINERJA ESG (ENVIRONMENTAL, SOCIAL, GOVERNANCE) & KINERJA KEUANGAN: EFEK MODERASI TATA KELOLA PERUSAHAAN - Najmi Nabila; Widya Perwitasari (EQUITY, 2025)
ESG is important factor in running a business, where its optimal implementation is believed to drive a company success and make it more attractive to investor. Through testing and analysis, this research investigates the relationship between the size of the board of directors and shareholder ownership concentration can moderate the relationship between ESG performance and financial performance. The sample uses data from 29 public companies in Indonesia operating outside the financial sector, for the period 2020-2024. The data was obtained from Refinitiv Eikon and company annual reports. The proxy variable for ESG performance in this study is the ESG Score, the number of board directors, and the top three largest shareholdings, the study aims to examine their influence in strengthening or weakening the relationship between ESG performance and financial performance. Empirical findings indicate that the effectiveness of ESG relationship and financial performance depends on the existence of a board of directors, but it is not influenced by concentrated share ownership structures. Keywords: ESG Performance; Board of Directors; Shareholder Ownership Concentration; Financial Performance.